Reactive Attitudes & the Value of Responsibility - (:unkn) unknown (My University, 2018)
This paper argues against the family of “reactive accounts” of moral responsibility. On such accounts, which take their cue from P.F. Strawson’s influential “Freedom and Resentment,” being morally responsible is properly understood in terms of being held responsible, which in turn is properly understood in terms of a set of moral emotions and their associated practices. This way of understanding responsibility re-frames apparently metaphysical questions about whether we are responsible in normative terms, as questions about whether and why these practices are permissible or required. I argue that we are responsible because we in some sense affirm the value of being held responsible, but that the reactive account fails to accommodate this fact about our responsibility. Specifically, this is the case because the moral emotions at issue do not seem to have a necessary connection to the way of regarding other people that must be implicit in our responsibility practices if we are to affirm their value. For one thing, there is no necessary connection between certain commitments and certain affective dispositions. For another, it is not hard to come up with instances in which these attitudes betray an obvious failure to share in the commitments that make responsibility practices valuable. Finally, I argue for the point that such a necessary connection between evaluative commitments and responsibility practices is crucial to a theory of the latter insofar as we want the theory itself to convey these commitments.
Keywords: emotions; reactive attitudes; responsibility